Use of Recombinant Antigens for the Diagnosis of Invasive Candidiasis - Ana Laín; Natalia Elguezabal; Elena Amutio; Iñigo Fernández de Larrinoa; María Dolores Moragues; José Pontón (Clinical and Developmental Immunology)
Invasive candidiasis is a frequent and often fatal complication in immunocompromised and critically ill patients. Unfortunately, the diagnosis of invasive candidiasis remains difficult due to the lack of specific clinical symptoms and a definitive diagnostic method. The detection of antibodies against different Candida antigens may help in the diagnosis. However, the methods traditionally used for the detection of antibodies have been based on crude antigenic fungal extracts, which usually show low-reproducibility and cross-reactivity problems. The development of molecular biology techniques has allowed the production of recombinant antigens which may help to solve these problems. In this review we will discuss the usefulness of recombinant antigens in the diagnosis of invasive candidiasis.